2015
DOI: 10.1007/s12010-015-1535-0
|View full text |Cite
|
Sign up to set email alerts
|

The Variations of Glycolysis and TCA Cycle Intermediate Levels Grown in Iron and Copper Mediums of Trichoderma harzianum

Abstract: The efficiency of optimal metabolic function by microorganism depends on various parameters, especially essential metal supplementation. In the present study, the effects of iron and copper metals on metabolism were investigated by determination of glycolysis and tricarboxylic acid (TCA) cycle metabolites' levels with respect to the metal concentrations and incubation period in Trichoderma harzianum. The pyruvate and citrate levels of T. harzianum increased up to 15 mg/L of copper via redirection of carbon flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The results were indicative of a complex interaction among iron homeostasis, cellular energy metabolism, and oxidative phosphorylation. 59 In order to investigate the effect of the nanoparticles on the fungus reproductive structures (Figure 3B), a comparison was made of the growth curves for the NPFe suspension and the fungus filtrate growth medium used to synthesize the NPFe (here called filtrate). The results showed that the growth kinetics was faster for NPFe than for the filtrate, indicating that the biogenic iron oxide nanoparticles stimulated the reproductive structures present in the nanoparticle suspensions, demonstrating that NPFe acted as a growth promoter for Trichoderma.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The results were indicative of a complex interaction among iron homeostasis, cellular energy metabolism, and oxidative phosphorylation. 59 In order to investigate the effect of the nanoparticles on the fungus reproductive structures (Figure 3B), a comparison was made of the growth curves for the NPFe suspension and the fungus filtrate growth medium used to synthesize the NPFe (here called filtrate). The results showed that the growth kinetics was faster for NPFe than for the filtrate, indicating that the biogenic iron oxide nanoparticles stimulated the reproductive structures present in the nanoparticle suspensions, demonstrating that NPFe acted as a growth promoter for Trichoderma.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Accumulation of copper is also well‐known to inhibit key enzymes of glycolysis resulting in cytoplasmic collection of surplus glucose [153] . In particular, high copper levels have been shown to alter the synthesis of pyruvate via inhibition of phosphofructokinase‐1 [15] . Variations in such interconvertible TCA cycle intermediate metabolites is demonstrated to directly influence energy production, making glutamic acid and α‐KG absolutely essential to sustain proliferation of cancer cells under hypoxic conditions [154] …”
Section: Metabolismmentioning
confidence: 99%
“…Insights from Wilson's Disease indicate that copper may play a role in the regulation of S‐adenosylmethionine (SAM) [8] essential for epigenetic modification [14] . Recent work in fungi has also highlighted the ability of copper to modulate the expression of key metabolites in the TCA cycle [15] whilst other studies have noted the altered metabolic profile of Wilson's Disease patients [16] . Cellular metabolism essentially represents a crossroads in which all these different mechanisms interact with one another, and therefore a vulnerability to exploit therapeutically.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, citrate plays a role in the regulation of cellular pH and as a carbon skeleton source [ 60 ]. Various organic acids including oxaloacetate, succinate, fumarate and malate, as TCA cycle intermediates are the precursors for various biosynthetic pathways, such as gluconeogenesis and amino acid synthesis [ 71 ]. Taken together these observations suggest a crucial role for the Fe valence state of Fe sources in cucumber metabolic responses to Fe deficiency.…”
Section: Discussionmentioning
confidence: 99%